2005
DOI: 10.1111/j.1365-2249.2005.02970.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent induction of IL-6 by plant-derived proteasesin vitro

Abstract: SummaryOral administration of proteases such as bromelain and papain is commonly used in patients with a wide range of inflammatory conditions, but their molecular and cellular mechanisms of action are still poorly understood. The aim of our study was to investigate the impact of these proteases on the release of interleukin-6 (IL-6) and other cytokines in the recently described modified mixed lymphocyte culture (MMLC) test system which is based on the mutual interaction of cells of the innate and adaptive imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
12
1
4
Order By: Relevance
“…In contrast to the current study, several in vitro studies have shown that bromelain treatment can actually increase production of pro-inflammatory cytokines such as IL-6, TNF, IFN-γ, GM-CSF by macrophages, NK cells, and mixed lymphocyte cultures (42)(43)(44). Additional studies are needed to address the mechanisms by which bromelain affects colon tissues.…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast to the current study, several in vitro studies have shown that bromelain treatment can actually increase production of pro-inflammatory cytokines such as IL-6, TNF, IFN-γ, GM-CSF by macrophages, NK cells, and mixed lymphocyte cultures (42)(43)(44). Additional studies are needed to address the mechanisms by which bromelain affects colon tissues.…”
Section: Discussioncontrasting
confidence: 92%
“…In addition to secondary metabolites, the proteolytic enzymes present in papaya (papain and chymopapain) have also shown immunomodulatory and anti-inflammatory activities (Rakhimov 2001;Rose et al 2006;Mohr & Desser 2013). The role of transforming growth factor (TGF)-b in anti-inflammation is evident.…”
Section: Anti-inflammatory Activities Of Papaya-associated Phytochemimentioning
confidence: 99%
“…Rose et al . () also report a dose‐dependent induction of IL‐6 production, while there was no effect on the production of IFNγ and IL‐10. On the other hand the investigations by Huang et al .…”
Section: Introductionmentioning
confidence: 89%